2018
DOI: 10.1016/j.jbiomech.2018.02.010
|View full text |Cite|
|
Sign up to set email alerts
|

A little bit faster: Lower extremity joint kinematics and kinetics as recreational runners achieve faster speeds

Abstract: There appears a linear relationship between small increases in running speed and cardiovascular health benefits. Encouraging or coaching recreational runners to increase their running speed to derive these health benefits might be more effective if their joint level kinematic and kinetic strategy was understood. The aim of this investigation was to compare the peak sagittal plane motions, moments, and powers of the hip, knee and ankle at 85%, 100%, 115% and 130% of self-selected running speed. Overground runni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
38
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 18 publications
7
38
0
1
Order By: Relevance
“…The effect of running speed on frontal plane knee kinematics is a further area of research to be explored. Orendurff et al (2018) found that as running speed increased so did peak knee flexion in the stance phase, as observed in the sagittal plane. If running speed were to also effect frontal plane knee kinematics, this may consequentially affect the strength of correlation to frontal plane kinematics during the SLS.…”
Section: Discussionmentioning
confidence: 92%
“…The effect of running speed on frontal plane knee kinematics is a further area of research to be explored. Orendurff et al (2018) found that as running speed increased so did peak knee flexion in the stance phase, as observed in the sagittal plane. If running speed were to also effect frontal plane knee kinematics, this may consequentially affect the strength of correlation to frontal plane kinematics during the SLS.…”
Section: Discussionmentioning
confidence: 92%
“…The influence of speed on joint kinetics during LR has been investigated across both recreational running speeds (2.5-3.5 m/s) 8,9 and very high speeds (~9 m/s). [10][11][12] In general, faster running speeds are associated with increased energy absorption/generation, 8 increased peak negative/positive power, [8][9][10][11][12] increased peak moments at all three joints, [9][10][11] and reduced cumulative energy absorption at the knee. 13 In general, graded running affects spatiotemporal parameters and these changes lead to changes in joint kinetics and to the relative contributions of each joint to overall negative/positive power.…”
Section: Introductionmentioning
confidence: 99%
“…Increased velocity is achieved initially through increasing step length, followed by increasing cadence [18]. In turn, the increase of step or stride length requires mechanically greater ROMs in the major participating joints of the lower extremities and trunk [19]. Thus, the increased spatiotemporal and angular joint parameters during sports bra use could be considered to reflect improvements or to be positive effects.…”
Section: Discussionmentioning
confidence: 99%